A Qualitative Analysis of Program Fidelity and Perspectives of Educators and Parents after Two Years of the Girls' Iron-Folate Tablet Supplementation (GIFTS) Program in Ghanaian Secondary Schools. Issue 7 (2nd July 2021) - Gosdin, Lucas; Amoaful, Esi Foriwa; Sharma, Deepika; Sharma, Andrea J; Addo, O Yaw; Ashigbi, Xoese; Mumuni, Braima; Situma, Ruth; Ramakrishnan, Usha; Martorell, Reynaldo; Jefferds, Maria Elena
ABSTRACT: Background: To address the burden of anemia in adolescent girls in Ghana, the Girls' Iron-Folate Tablet Supplementation (GIFTS) program was established in 2017. An evaluation found that although iron and folic acid (IFA) supplementation reached nearly all adolescent girls in schools during year 1, most girls received fewer than the minimum effective number of tablets over the school year. Barrier analyses highlighted schools as drivers of adherence, though information was incomplete on the reasons for the disparities among schools. Information was also lacking on the implementation of health and nutrition education. Objectives: At the start of year 3 of an integrated adolescent anemia prevention program with IFA supplementation, the present study sought to illuminate differences in program fidelity among schools and across time and potential factors that drive such differences. Methods: After stratifying by school level, size, geographic location, and intake adherence during year 1, 16 schools were purposively selected. For each school, semistructured key informant interviews were conducted with 1 coordinator at the district level, 3 educators at the school level, and 1 parent leader. Following thematic analysis methods, recorded and transcribed interviews were coded and organized into deductive and inductive themes. Results: Limited training, challenges during distribution of IFA, lack of incentives, and inconsistent health and nutrition education diminished program fidelity. Strong supply chain, widespread awareness promotion, improved acceptability, and intrinsically motivated educators improved program fidelity. After 2 y of implementation, schools had made program adaptations, and widespread changes in attitudes and beliefs about the IFA tablets had improved their acceptability. However, limitations remained related to supply chain, program ownership, communication between health and education sectors, training, motivation, and resources. Conclusions: The fidelity of Ghana's GIFTS program is strengthened by its supply chain, acceptability, and motivated stakeholders; however, training, curricula, clear communication, and incentives could improve it. Abstract : After 2 y of implementation, a school-based anemia prevention program with iron–folic acid supplementation is accepted by educators and parents in Ghana, yet some limitations to fidelity remain.